Synthetic Creativity and the Recomposition of Brand Value: A Dynamic Capability Perspective on Generative AI Intensification - Romli (Manexia: Journal of Business, Management, and Creative Economy, 2025)
The diffusion of generative AI challenges foundational assumptions in branding and strategic management. Classical brand theory conceptualizes differentiation as the outcome of human-authored creativity, while dynamic capabilities scholarship emphasizes costly exploration and managerial orchestration as the basis of sustained advantage. Generative AI disrupts these premises by enabling large-scale probabilistic recombination of symbolic content at marginal cost. This article advances a conceptual re-theorization of creativity under such conditions by introducing synthetic creativity as an orchestrated dynamic capability through which firms govern probabilistic generative systems to sustain symbolic differentiation. Integrating dynamic capabilities theory, exploration–exploitation logic, organizational learning, and AI research, a mechanism-based model is developed to explain how generative AI intensification produces non-linear effects on brand value. Three interdependent mechanisms are specified: exploration compression, capability substitution versus augmentation, and metric-driven symbolic over-optimization. Together, these mechanisms generate a curvilinear relationship between AI intensification and brand differentiation, moderated by data heterogeneity, governance architecture, and infrastructural control. By shifting analytical focus from AI adoption to orchestration asymmetry, the study reconceptualizes competitive advantage in symbolic markets as dependent on governance of probabilistic infrastructures rather than on ideational originality. The framework establishes theoretical foundations for examining strategic differentiation in the generative economy.